EVALUASI TINGKAT PENGETAHUAN DAN RASIONALITAS SWAMEDIKASI DENGAN KARAKTERISTIK MASYARAKAT - Anggraini, Herlina (Journal of Pharmacy Tiara Bunda, 2021)
Self-medication is a process carried out by a person starting form the introduction of complaint or symptoms and oon the selection and use of drugs. The diseases are: fever, pain, colds and flu, cough, gastritis, diarrhea. The problem that often occurs is the lack of public knowledge rational certification. This study was conducted to evaluate the level of publik knowledge of self—medication and rationality of drug usage by providing educaton so that there is an increase in public understanding and knowlegde about good self-medication. Cross-sectional descriptive research method. Data were taken secondary through filling out the questionnaire, there were 9 people in Pengasinan Sawangan District selected by accidental sampling method. Data were processed using the statistical product and service solution (SPSS) application version 22 with a chi-square test. The results of the study stated that the level of public know ledge of 22.80% is good, 44.30% is moderate and 32.90% is poor. 70.90% of the majority of people use drigs rationlally and 29.10% are not rational. There is a relationship between age and last education with the level of knowledge andd rrationality in using self-medication drugs. However, it has nothing to do with sex and occcupation. Based on the results ot the study are that the level of public know ledge is moderate, 44.30% and the rationality of drug use is rational 70.90%